Crises and Prices: Information Aggregation, Multiplicity, and Volatility - Angeletos, George-Marios; Werning, Iván (American Economic Review, 2006)
Crises are volatile times when endogenous sources of information are closely monitored. We study the role of information in crises by introducing a financial market in a coordination game with imperfect information. The asset price aggregates dispersed private information acting as a public noisy signal. In contrast to the case with exogenous information, our main result is that uniqueness may not obtain as a perturbation from perfect information: multiplicity is ensured with small noise. In addition, we show that: (a) multiplicity may emerge in the financial price itself; (b) less noise may contribute toward nonfundamental volatility even when the equilibrium is unique; and (c) similar results obtain for a model where individuals observe one another?s actions, highlighting the importance of endogenous information more generally. (JEL D53, D82, D83)